Anaesthesia geriatric evaluation to guide patient selection for preoperative multidisciplinary team care in cardiac surgery. (April 2020) - Verwijmeren, Lisa; Peelen, Linda M.; van Klei, Wilton A.; Daeter, Edgar J.; van Dongen, Eric P.A.; Noordzij, Peter G.
Abstract: Background: A multidisciplinary approach to improve postoperative outcomes in frail elderly patients is gaining interest. Multidisciplinary team care should be targeted at complex patients at high risk for adverse postoperative outcome to limit the strain on available resources and to prevent an unnecessary increase in patient burden. This study aimed to improve patient selection for multidisciplinary care by identifying risk factors for disability after cardiac surgery in elderly patients. Methods: This was a two-centre prospective cohort study of 537 patients aged ≥70 yr undergoing elective cardiac surgery. Before surgery, 11 frailty characteristics were investigated. Outcome was disability at 3 months defined as World Health Organization Disability Assessment Schedule 2.0 ≥25%. Multivariable modelling using logistic regression, concordance statistic (c-statistic), and net reclassification index was used to identify factors contributing to patient selection. Results: Disability occurred in 91 (17%) patients. Ten out of 11 frailty characteristics were associated with disability. A multivariable model, including the European System for Cardiac Operative Risk Evaluation II and preoperative haemoglobin, yielded a c-statistic of 0.71 (95% confidence interval [CI]: 0.66–0.77). After adding pre-specified frailty characteristics (polypharmacy, gait speed, physical disability, preoperative health-related quality of life, and living alone) to this model, the c-statistic improved to 0.78 (95% CI: 0.73–0.83). The net reclassification index was 0.32 ( P <0.001), showing improved discrimination for patients at risk for disability at 3 months. Conclusions: The addition of preoperative frailty characteristics to a multivariable model improved discrimination between elderly patients with and without disability at 3 months after cardiac surgery, and can be used to guide patient selection for preoperative multidisciplinary team care. Clinical trial registration: NCT02535728 .